Pengaruh Tax Avoidance dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Dengan Transparansi Perusahan Sebagai Variabel Moderasi - Ramadia, Novita; Utami, Tri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara, 2024)
This research aims to analyze the influence of Tax Avoidance and Managerial Ownership on Company Value with Company Transparency as a Moderating Variable in Energy Sector Companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The data used in this research is secondary data, namely the company's annual financial report. The type of research used is quantitative research. The population of this study was 87 Energy Sector Companies and the sampling method used was purposive sampling. The number of samples in this research was 13 companies with observations for 5 years, so 65 objects of observation were selected. The analysis technique used is interaction analysis to test the effect of moderating variables and panel data regression analysis using a fixed effect regression model. The data was processed using Microsoft Office Excel and Eviews 13 software applications. The results showed that tax avoidance and managerial ownership simultaneously have an effect on company value, tax avoidance has no effect on company value, managerial ownership has an effect on company value, company transparency can not to moderate the effect of tax avoidance on company value and company transparency can to moderate (weaken) the effect of managerial ownership on company value.